Arquitectura Inteligente CPPS Integrada en el Uso de la Norma IEC-61499, con Bloque de Funciones Altamente Adaptables en la Industria 4.0 - Murillo, Félix M.; Díaz, Darío J. (KnE Engineering, 2018)
Today, we are experiencing what it is being labelled as the Fourth Industrial Revolution (Industry 4.0) in terms of automation and control systems of cyber - physical production environments. These systems not only allow access to many innovative features based on network connections, but they also provide access to the world of the Internet of Things (IoT). It is in this context that IoT changes the ways to link new technologies in order to obtain more efficient, intelligent, flexible and adaptable production systems; thus becoming an interdependence of the product itself that the companies wish to commercialize. Cyber- Physical Production Systems (CPPS) have the advantages of granular communications, common electric bandwidth for all users regardless of data speeds, compatibility in connection with free or guided space communication links and with the major compatibility with intensity modulation. IEC 61499 is generally based on a generic architecture, with specific software requirements, development rules that allow for portability and device configuration. Keywords: IoT, configuration, communication, CPPS, Industry 4.0, smart.